Juridical Analysis Of Doctors' Responsibilities For Malpractic Action - Fernandez, M. Rizky; Muhibbin, Moh.; Arief, Hanafi (Scholar Center, 2023)
This study aims to describe the criminal liability of doctors who commit malpractice acts and to analyze the legal protection for patients who are victims of malpractice in positive law studies in Indonesia. This study uses normative legal research using three types of legal materials related to the responsibility of doctors for malpractice actions, namely primary legal materials, secondary legal materials and tertiary legal materials, with the nature of qualitative descriptive research, types of normative juridical research, statutory and conceptual approaches. The results of the study stated that malpractice is included in the realm of criminal law other than civil and administrative. Doctors can be prosecuted criminally, although the criminal law does not clearly stipulate criminal penalties for malpractice. However, several conventional articles in the Criminal Code implicitly mention provisions regarding malpractice that can be used as a basis for criminal charges. In the Criminal Code, criminal liability for malpractice is contained in Article 90, Article 359, Article 360 ??paragraphs (1) and (2) and Article 361. Those subject to this article include doctors, midwives, medicine experts, who are experts in their work. each. If they ignore the regulations or requirements in their work, causing death (Article 359) or serious injury (Article 360), they will be punished more severely. Legal protection for victims of medical malpractice is regulated in Law no. 29 of 2009 concerning Medical Practice, granting rights to victims to submit complaints to the Chairman of the Indonesian Medical Discipline Honorary Council, as well as simultaneously taking criminal and civil law remedies to court.